2020
DOI: 10.1111/echo.14657
|View full text |Cite
|
Sign up to set email alerts
|

Independence of coronary artery disease to subclinical left ventricular dysfunction

Abstract: Objective: Epicardial atherosclerosis and heart failure while distinct clinical entities share common pathophysiological features including endothelial dysfunction and inflammation. Presence of subclinical disease could lead to early diagnosis and intervention in the other. The aim of our study was to assess the association between coronary calcium score (CCS), conventional cardiovascular risk factors, and echocardiographic markers of subclinical left ventricular dysfunction (S-LVD). Methods: One hundred and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Moreover, researchers showed differences in age and BMI between groups with and without LVDD as opposed to our study. There were no age, gender, blood pressure, or BMI differences between population with and without LVDD, similarly to the population with low-intermediate risk of CAD [8]. Our findings which demonstrate a correlation between the presence of LVDD and LVMI are in line with the earlier studies [4,19,22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, researchers showed differences in age and BMI between groups with and without LVDD as opposed to our study. There were no age, gender, blood pressure, or BMI differences between population with and without LVDD, similarly to the population with low-intermediate risk of CAD [8]. Our findings which demonstrate a correlation between the presence of LVDD and LVMI are in line with the earlier studies [4,19,22].…”
Section: Discussionsupporting
confidence: 91%
“…Venkataraman [8] showed that 9.6% of participants with low-intermediate risk of coronary artery disease (CAD) had LVDD, and atherosclerosis was not directly associated with subclinical LV dysfunction. In present study, all participants had CAD, the population was older, BMI was higher and LVEF was lower compared to the above mentioned study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Scholte et al [ 8 ] showed that patients with T2DM with coronary atherosclerosis exhibited reduced GLS compared to patients with T2DM and no coronary atherosclerosis. Another study by Venkataraman et al [ 31 ] investigated the association among CAC, conventional cardiovascular risk factors and subclinical left ventricular dysfunction in patients with a low-intermediate risk of CAD. They concluded that atherosclerosis was not associated with subclinical LV dysfunction, and the findings indicated no linear relationship in a low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The participants presenting with chest pain with normal coronaries on angiography and non-obstructive disease accepted as control may have microvascular coronary artery disease affecting the control GLS values, leading to underestimation of the difference between the disease and control group. Studies have shown that patients with coronary microvascular disease are known to have a significant lowering of coronary reserves, thus affecting patterns of GLS [ 2 , 3 ]. Thereby, this should be taken into consideration when interpreting the results of this study.…”
mentioning
confidence: 99%